Successful treatment with lithium carbonate for periodic psychosis of adolescence - Rikuto Christopher Shinohara; Keisuke Inoue; Shun Takayanagi; Yoichi Furutaka; Hikari Yamazaki; Shinya Watanabe (PCN Reports, 2025)
Abstract Background Periodic psychosis of adolescence is a rare psychiatric condition observed in adolescent girls, characterized by recurrent episodes of diverse psychiatric symptoms, including behavioral inhibition, excitement, hyperactivity, hallucinations, and delusions. These episodes closely align with the menstrual cycle. Mood stabilizers, such as lithium carbonate, have demonstrated efficacy in managing this condition. Case Presentation We report the case of a 14‐year‐old adolescent girl with periodic psychosis, successfully treated with lithium carbonate. Her symptoms first appeared at age 12 as transient episodes of insomnia, anxiety, and depressive mood. By age 14, she developed hallucinations and persecutory delusions, leading to hospitalization. Initial treatment with risperidone and aripiprazole was discontinued due to suspected neuroleptic malignant syndrome. During hospitalization, she experienced three distinct psychiatric cycles, each comprising a 2‐week period of severe excitement, hyperactivity, hallucinations, and disorganized thinking, followed by a sudden decline in activity levels, with anxiety and fear becoming predominant. Despite adequate treatment with quetiapine and olanzapine, episodes continued to recur. Given the strong correlation between her psychiatric symptoms and menstrual cycle, she was diagnosed with periodic psychosis of adolescence. Lithium carbonate was introduced to prevent further cyclical episodes. The patient was discharged on day 153 of hospitalization. Six months after discharge, she had no recurrence of psychiatric symptoms. Conclusion This case underscores the potential efficacy of lithium carbonate for periodic psychosis of adolescence and the importance of understanding this rare but distinctive psychiatric condition.